+0  
 
0
98
1
avatar

Given: m∠A + m∠B = m∠B + m∠C

Prove: m∠C = m∠A

Write a paragraph proof to prove the statement. 

Guest Aug 14, 2018
 #1
avatar+88775 
+1

If m∠A + m∠B = m∠B + m∠C, subtract  m∠B from both sides  [ subtraction property of equality ].

We get that m∠A  = m∠C     and by the  symmetric property of equality,  m∠C = m∠A

 

 

cool cool cool

CPhill  Aug 14, 2018

42 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.